1998
DOI: 10.1002/(sici)1522-7189(199811/12)6:6<235::aid-nt26>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Fluorometric HPLC Determination of 1‐Desulfoyessotoxin, a New Yessotoxin Analog Isolated from Mussels from Norway

Abstract: A new analog of yessotoxin, 1-desulfoyessotoxin, was isolated from the digestive glands of mussels growing in the Sognefjord, Norway. Its structure was determined by NMR and negative ion CID MS/MS experiments. 1-Desulfoyessotoxin can be detected by the fluorometric HPLC method analogous with other yessotoxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Subsequently, YTX production by P. reticulatum collected in Japan, Italy, Norway, and Spain was also confirmed (Ciminiello et al, 2003;Eiki et al, 2005;MacKenzie et al, 2002;Paz et al, 2004;Samdal et al, 2004;Satake et al, 1999). Many different analogs, 45,46,homoYTX,adriatoxin,carboxyYTX,carboxyhomoYTX,YTX amide analogs,44,www.elsevier 44,44,46,46, were isolated and detected from bivalves and P. reticulatum (Ciminiello et al, 1998(Ciminiello et al, , 2000a(Ciminiello et al, ,b, 2001(Ciminiello et al, , 2002(Ciminiello et al, , 2003Daiguji et al, 1998;Finch et al, 2005;Miles et al, 2004aMiles et al, ,b, 2005Miles et al, , 2006Morohashi et al, 2000;Satake et al, 1996Satake et al, , 1997b. Of these analogs, homoYTX, 45-hydroxyhomoYTX, carboxyhomoYTX, and heptanor-41-oxohomoYTX were often observed in mussels of the Adriatic Sea (Ciminiello et al, 1999;Draisci et al, 1999;Satake et al, 1997a), however, homoYTX analogs have never been found in Japan.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequently, YTX production by P. reticulatum collected in Japan, Italy, Norway, and Spain was also confirmed (Ciminiello et al, 2003;Eiki et al, 2005;MacKenzie et al, 2002;Paz et al, 2004;Samdal et al, 2004;Satake et al, 1999). Many different analogs, 45,46,homoYTX,adriatoxin,carboxyYTX,carboxyhomoYTX,YTX amide analogs,44,www.elsevier 44,44,46,46, were isolated and detected from bivalves and P. reticulatum (Ciminiello et al, 1998(Ciminiello et al, , 2000a(Ciminiello et al, ,b, 2001(Ciminiello et al, , 2002(Ciminiello et al, , 2003Daiguji et al, 1998;Finch et al, 2005;Miles et al, 2004aMiles et al, ,b, 2005Miles et al, , 2006Morohashi et al, 2000;Satake et al, 1996Satake et al, , 1997b. Of these analogs, homoYTX, 45-hydroxyhomoYTX, carboxyhomoYTX, and heptanor-41-oxohomoYTX were often observed in mussels of the Adriatic Sea (Ciminiello et al, 1999;Draisci et al, 1999;Satake et al, 1997a), however, homoYTX analogs have never been found in Japan.…”
Section: Introductionmentioning
confidence: 96%
“…1) was first isolated from the scallop, Patinopecten yessoensis in Japan, and its structure was elucidated by NMR spectroscopy and by negative ion FAB CID MS/MS experiments (Murata et al, 1979;Naoki et al, 1993;Satake et al, 1996;Takahashi et al, 1996). Occurrences of YTX and its analogs outside of Japan have occurred in Norway (Lee et al, 1988;Daiguji et al, 1998), Italy (Ciminiello et al, 1997;Satake et al, 1997a;Ciminiello et al, 1998Ciminiello et al, , 1999Draisci et al, 1999), Chile, New Zealand (Yasumoto and Takizawa, 1997), and Canada (Finch et al, 2005). The dinoflagellate Protoceratium reticulatum collected in New Zealand was first identified as the biogenetic origin of YTX (Satake et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Yessotoxins are www.elsevier.com/locate/hal Harmful Algae 4 (2005) [1075][1076][1077][1078][1079][1080][1081][1082][1083][1084][1085][1086][1087][1088][1089][1090][1091] produced by the dinoflagellate algae Protoceratium reticulatum (Ciminiello et al, 2003;Samdal et al, 2004a;Satake et al, 1997aSatake et al, , 1999 and Lingulodinium polyedrum (Draisci et al, 1999;Paz et al, 2004). Filter-feeding shellfish accumulate and produce metabolites of YTXs, many of which are toxic by intraperitoneal injection (Ciminiello et al, 1998(Ciminiello et al, , 2000Daiguji et al, 1998;Murata et al, 1987;Satake et al, 1996Satake et al, , 1997bTerao et al, 1990) and therefore give rise to positive results in the traditional mouse bioassay for lipophilic biotoxins. Because of this, the maximum permissible level of YTX (1) and 45-hydroxyYTX (2) and their 1a-homo congeners (4 and 45-hydroxy-4) in shellfish in the EU is 1000 mg/kg (European Union, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Yessotoxin (YTX), a disulfated polyether toxin, was first identified in scallops from Japan, Patinopecten yessoensis, for which the toxin class was named (Murata et al, 1987). Since its discovery, close to 90 other analogs have been identified (Satake et al, , 1999Ciminiello et al, 1998Ciminiello et al, , 2000Ciminiello et al, , 2001Daiguji et al, 1998;Miles et al, 2004Miles et al, , 2005aMiles et al, , 2005bMiles et al, , 2006Finch et al, 2005;Paz et al, 2006). There are three known biological origins of YTX, the dinoflagellates, Protoceratium reticulatum (Claparhde and Lachmann) Buetschli, Lingulodinium polyedrum (Stein) Dodge, and Gonyaulax spinifera (Claparede et Lachmann) Diesing.…”
Section: Introductionmentioning
confidence: 99%